2021
DOI: 10.3389/fpsyg.2020.623587
|View full text |Cite
|
Sign up to set email alerts
|

Social Support Mediates the Effect of Burnout on Health in Health Care Professionals

Abstract: Burnout is characterized by emotional exhaustion and caused by exposure to excessive and prolonged stress related to job conditions. Moreover, burnout is highly prevalent among health care professionals. The aim of this study is, first, to examine the mediating role of social support over the effect of burnout in health care professionals and, second, to explore potential gender differences. A convenience sample of 1,035 health professionals from Ecuador, including 608 physicians and 427 nurses (68% women, wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
31
0
5

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(41 citation statements)
references
References 60 publications
5
31
0
5
Order By: Relevance
“…Collectively, these findings are consistent with recent studies of nurses which found an inverse association between PTG and burnout ( Hamama-Raz et al., 2021 ), and that religion/spirituality is negatively associated with burnout ( Harris and Tao, 2021 ; Zhang et al., 2019 ). They also align with prior research underscoring the importance of social support on burnout risk in health care personnel ( Bellanti et al., 2021 ; Cyr et al., 2021 ; Galanis et al., 2021 ; Ruisoto et al., 2020 ), and that spirituality, particularly positive spiritual coping, is associated with lower rates of PTSD and related mental health outcomes ( González-Sanguino et al., 2020 ; Sharma et al., 2017 ; Smith-MacDonald et al., 2017 ). Given that PTG, burnout, and PTSD symptoms were both assessed cross-sectionally at W2 in the current study, it is possible that these aspects of PTG may help mitigate risk for these outcomes, that lower severity of burnout or PTSD symptoms may lead to greater PTG in these domains, or that these variables may evolve in a complex and dynamic manner.…”
Section: Discussionsupporting
confidence: 85%
“…Collectively, these findings are consistent with recent studies of nurses which found an inverse association between PTG and burnout ( Hamama-Raz et al., 2021 ), and that religion/spirituality is negatively associated with burnout ( Harris and Tao, 2021 ; Zhang et al., 2019 ). They also align with prior research underscoring the importance of social support on burnout risk in health care personnel ( Bellanti et al., 2021 ; Cyr et al., 2021 ; Galanis et al., 2021 ; Ruisoto et al., 2020 ), and that spirituality, particularly positive spiritual coping, is associated with lower rates of PTSD and related mental health outcomes ( González-Sanguino et al., 2020 ; Sharma et al., 2017 ; Smith-MacDonald et al., 2017 ). Given that PTG, burnout, and PTSD symptoms were both assessed cross-sectionally at W2 in the current study, it is possible that these aspects of PTG may help mitigate risk for these outcomes, that lower severity of burnout or PTSD symptoms may lead to greater PTG in these domains, or that these variables may evolve in a complex and dynamic manner.…”
Section: Discussionsupporting
confidence: 85%
“…In this sample, high prevalence of symptoms associated with burnout, such as low personal accomplishment (17.3%) and emotional exhaustion (16.3%) are reported, which are very similar to those reported in health workers in Ecuador [ 45 ]. In non-crisis situations, this could be associated with deficiencies in their training to cover emergencies and that one out of eight perceives low social support—this factor has demonstrated its ability to influence emotional exhaustion in health workers in Ecuador [ 55 ]. Finally, Post-Traumatic Stress Disorder also occurs with a prevalence of 11.2%, which is much higher than that reported (7.2%) in the meta-analysis of [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…A sample item was “My job has too many demands”. Internal consistency for this study was good, with a Cronbach’s α of α = 0.89 for EE, α = 0.60 for depersonalization and α = 0.71 for PA [ 53 , 54 ], The following cut-off points were used EE > 26; Depersonalization > 9 and PA < 14; Brief scale to diagnose Post-Traumatic Stress Disorder [ 55 , 56 ], which consists of 12 items that are answered on a Likert scale from 0 (Not at all) to 3 (Very much). The cut-off points in relation to the level of emotional risk for post-traumatic stress are: Low presence of post-traumatic stress (0–3 points), Risk of post-traumatic stress (4–5 points) and post-traumatic stress (6–12 points).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In this line, individual differences like some personality factors or previous life experiences would impact on the ability to modulate the stress response making some people more vulnerable (Saravanan and Wilks, 2014;Hood et al, 2015). In the confrontation of a OSCE scenario in which the students' clinical abilities are evaluated is expected an autonomous sympathetic activation, as previous studies reported (Sánchez-Conde et al, 2019), causing an increase in blood pressure and heart rate, the liberation of cortisol that would negatively affect neurons communication in pre-frontal cortex, fact that could negatively affect cortical process as memory, attention, planning, decision making or reflective thinking (Diamond, 2013;Starcke et al, 2016;Beltrán-Velasco et al, 2020;Mendoza-Castejón and Clemente-Suárez, 2020;Mendoza-Castejon et al, 2020;Ruisoto et al, 2021). Then, to minimize the negatives effect of stress in students, the complex or difficult scenarios must be place after easier ones.…”
Section: Discussionmentioning
confidence: 85%